Sociolinguistic Survey of the Mal-Prai (“Lua”) speech varieties spoken in Nan Province, Thailand - Jeske, Alexander; Statezni, Carey (Journal of Integrative and Innovative Humanities, 2025)
This article shares the results of the sociolinguistic survey of the “Lua Bo Kluea” (LBK) speech community in Bo Kluea District, Nan Province, Thailand. The survey research aimed to further investigate the language situation of the “Lua Bo Kluea” speech community in Bo Kluea District, Nan Province, Thailand, building on the research documented in (Jeske, 2022) and filling in the gaps from that research. The first purpose of the research was to assess how well the “Lua Bo Kluea” understand the Prai ‘R/Y’ speakers of Chiang Klang District, since this closely-related speech variety already has a written form and a body of literature materials available. If the LBK speakers do understand Prai ‘R/Y’ adequately, the second purpose was to assess the attitudes towards the Prai ‘R/Y’ language variety and its speakers. If the attitudes are positive, the next step was to assess if the “Lua Bo Kluea” would consider using the existing Prai ‘R/Y’ literature materials. The research methods included comprehension testing, dialect mapping and interviews regarding LBK speakers’ comprehension of and attitudes towards the Prai ‘R/Y’ speech variant which already has a body of literature. Results showed low tested comprehension (RTT village average scores ranging from 58% to 78%, with an overall average score of 71%). Results also showed low perceived comprehension, low levels of contact, communication difficulties, and a high perceived degree of difference between these speech varieties. Thus, we conclude that the Lua people from Bo Kluea District cannot understand the Prai ‘R/Y’ speech variety adequately without some type of adaptation, training, or more contact promotion. The people from Bo Kluea District generally have positive attitudes toward the Prai ‘R/Y’ people. They identify as part of the same ethnic and linguistic group and are open to intermarriage among them. However, both adaptation (checking the words, expressing it in the LBK dialect) and literacy training (teaching people to read the script) would be needed in order to be able to use the existing Prai literature materials in their communities.